On the security of reliable server pooling systems. (16th November 2010) - Dreibholz, Thomas; Zhou, Xing; Becke, Martin; Pulinthanath, Jobin; Rathgeb, Erwin; Du, Wencai
In order to cope with the requirements of availability-critical internet services, reliable server pooling (RSerPool) has been developed as the new IETF standard for a lightweight server redundancy and session failover framework. While the service and pool management performance of RSerPool had already been the topic of various research papers, its security has not yet been widely examined. But security for availability-critical systems is crucial, since service outages – regardless of whether being caused by system failures or intentional denial of service (DoS) attacks – are not acceptable for the users of such systems. In this article, we first introduce RSerPool as well as the underlying SCTP protocol. In an analysis of the attack threats, we will show the possibilities of an attacker to degrade the service provided by an RSerPool system. We will furthermore introduce possible countermeasures, in order to prevent attacks and improve the robustness of the systems. We will finally show the effectiveness of our proposed countermeasures using simulations. In order to validate our simulation results, we furthermore compare them to measurements from a real-world internet setup using the PlanetLab.